The cosmopolitan elite in Germany: transnationalism and postmaterialism. (5th March 2015) - HELBLING, MARC; TENEY, CÉLINE
Abstract In this article, we investigate cosmopolitan attitudes among the people often considered the most cosmopolitan – the elite. Studying the typical class of frequent travellers provides a particularly good opportunity to study the relationship between transnational activities and cosmopolitanism. We also comprehensively investigate the link between postmaterialist values and cosmopolitan attitudes. We test our arguments using an original dataset that includes a relatively large sample of the German positional top elite in the years 2011 and 2012. A comparison between these data and data from a general population survey shows that while transnational activities affect the attitudes of ordinary citizens, increased travelling does not make elites more cosmopolitan. We discuss several reasons why this might be the case. We also observe that postmaterialist values and the ideological environment of the elite play a key role. Finally, we tentatively suggest that cosmopolitan elites do not endanger national social cohesion, as some fear they might. We show that cosmopolitanism and localism are not mutually exclusive and that members of the German elite feel even more attached to their nation than ordinary Germans.